2000
DOI: 10.1046/j.1440-1681.2000.03242.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenic Rats For Hypertension: How Useful Are They For The Hunting Of Hypertension Genes?

Abstract: SUMMARY Linkage studies have revealed quantitative trait loci (QTL)for blood pressure in the rat genome using genetic hypertensive rat models. To identify the genes responsible for hypertension, the construction of congenic rats is essential.2. To date, several congenic strains have been obtained from spontaneously hypertensive or Dahl salt-sensitive rats. The results of these studies should be interpreted according to whether the rats carry the whole QTL region or not.3. After establishing congenic strains, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…16 Our analysis finds that this difference is sustained across the 3 SHR substrains examined. This gene has been thoroughly studied because of its differential expression, its position in a wellsubstantiated SHR BP QTL, [17][18][19][20][21] evidence of polymorphism in the Sa locus between SHR and WKY, 22,23 and evidence from human studies suggesting involvement in BP determination. 24 -26 Recent rat congenic studies have not found support for the involvement of Sa in BP regulation.…”
Section: Discussionmentioning
confidence: 99%
“…16 Our analysis finds that this difference is sustained across the 3 SHR substrains examined. This gene has been thoroughly studied because of its differential expression, its position in a wellsubstantiated SHR BP QTL, [17][18][19][20][21] evidence of polymorphism in the Sa locus between SHR and WKY, 22,23 and evidence from human studies suggesting involvement in BP determination. 24 -26 Recent rat congenic studies have not found support for the involvement of Sa in BP regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Overnight urine samples were collected from groups of 4-5 adult mice in flasks containing tri phenylphosphine (2-3 mg each) (30). After adding synthetic [20 2 H3]-labeled 8,9; 11,12; and 14,15EET (5 ng each) and [5,6,8,9,11,12, and 14,15 2 H8]-labeled 8,9; 11,12; and 14,15DHET (5 ng each) as internal standards, the urine EETs and DHETs were extracted with acidified CHCl3/CH3OH (2:1) (24), purified by reverse phase HPLC as described (24), and methylated by reaction with diazomethane in ethyl ether (24). The resulting methylEETs and methylDHETs were quantified by LC/MS/MS using an Agilent Eclipse XDBC8 column (2.1 × 150 mm; 5 mm) connected to a TSQQuantum MS/MS spectrometer (Thermo Electron Corp.).…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies identified members of the P450 CYP2C and CYP4A gene sub families as functionally relevant AA epoxygenases and ωhydroxy lases, respectively (8)(9)(10)(11), and implicated them in the control of renal function and blood pressure (9)(10)(11). However, the unequivocal inter pretation of these studies is complicated by the in vitro nature of the functional data available (8)(9)(10)(11) and genetic complexity of the animal models studied (9)(10)(11)(12)(13). Consequently, notwithstanding their poten tial clinical importance, the physiological role of these enzymes in blood pressure regulation remains ambiguous and in need of experi mental confirmation.…”
Section: Introductionmentioning
confidence: 99%
“…The WKY-based congenic strain, WKY.SHRSP-(D1Wox29-D1Arb21)/Izm (abbreviated as WKYpch1.0 hereafter), was established by the transfer of the chromosomal segment between D1Wox29 and D1Arb21 from SHRSP onto the genetic background of WKY as previously described (10). The SHRSP-based congenic rat, SHRSP.WKY-(D1Wox29-D1Arb21)/Izm (abbreviated as SHRSPwch1.0), was designed to possess the genomic composition corresponding to that of the WKYpch1.0 (11).…”
Section: Animalsmentioning
confidence: 99%